Peningkatan kemampuan menulis karangan deskripsi dengan menggunakan peta konsep bagi siswa kelas VI SDN 44 Lubuk Anau Kecamatan Bayang - Ermaneli Ermaneli (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
This classroom action research is conducted to improve the writing ability of elementary school students. The reality in the field that applies conventional learning leads to saturation in students so that the negative impact on the ability to write the essay of the students. Use of concept maps can improve the ability to write essay writing elementary school students, in writing essay description. Based on the results of the study the use of concept maps proved to improve the ability to write an essay description of the students concerned. The enhancement of the writing ability of this description can be seen from the quality of the essay produced by the students, both in terms of capitalization, punctuation, ideas / ideas presented, and the demands of sentences used.